Trade liberalization and foreign direct investment in Malaysia - Nordin, Sabariah; Yusoff, Mohammed; Mat Ghani, Gairuzazmi (2015)
A decision to establish foreign direct investment (FDI) involves a lot of critical thinking, especially in deciding a place to locate the investment. Evaluation and consideration comprise of costs and benefits of launching the FDI. This study focuses on time series data for the sample period of 1970 to 2009. The main objective of this study is to identify the major determinant of the inward flows of FDI for Malaysia by employing the bounds testing (ARDL) approach to cointegration. Of all the variables being tested, trade openness is found to be the most influential variable in attracting the inflows of FDI as it shows consistent results in the short run as well as in the long run in all models being tested. Since the trade openness which represents the liberalization of the Malaysian economy could induce the inflows of FDI, some policy actions can be taken up to enhance the trade openness.